Predicting VO2max in competitive cyclists: Is the FRIEND equation the optimal choice? - Jurov, Iva; Cvijić, Marta; Toplišek, Janez (Frontiers in Physiology, 2023)
Predicting VO2max in athletes is vital for determining endurance capacity, for performance monitoring, in clinical diagnostic procedures, and for disease management. The aim of this study was to assess the most suitable equation for predicting VO2max in competitive cyclists. Competitive cyclists (496 males, 84 females, Caucasian, 580 total) were included in the study from January 1, 2014 to December 31, 2019. Only subjects who were actively participating in the national or international competitions, and were registered competitive cyclists and part of cycling teams at the time of the measurements were included. Subjects performed an incremental test on a cycle ergometer and VO2max was measured indicated by a plateau in VO2. In addition, four prediction equations (the FRIEND, Storer, Fairbarn, and Jones) were used to estimate VO2max. The predicted VO2max using FRIEND equation was in good agreement with the measured VO2max in male and female athletes. This was reflected by a high correlation with r=0.684 for males and r=0.897 for females (p=0.000), with ICC= 0.568 (95% CI 0.184,0.752) for males and ICC= 0.881 (95% CI 0.813,0.923) for females. Total error was 1.56 and 1.48 ml/min/kg and a minimal bias of – 3.6 and -1.1 ml/min/kg (males and females, respectively). Using other equations resulted in a slight decline in agreement with the measured standard. The FRIEND equation predicted VO2max accurately with small total error, small prediction errors and with the smallest constant error in our study cohort, indicating the potential value of using FRIEND equitation also in competitive cyclists. This equation proved to have the highest accuracy both in male and female cyclists.